1997
DOI: 10.1038/sj.onc.1201381
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Calu-1 human lung carcinoma cell growth in serum-free medium by retinoids: dependence on AP-1 activation, but not on retinoid response element activation

Abstract: Many lung cancer cell lines are resistant to the growth inhibitory eects of retinoids. However, some small-cell lung cancer cell lines were inhibited by all trans-retinoic acid (ATRA) in serum-free medium. We compared the responses of seven non-small cell lung cancer (NSCLC) cell lines to ATRA in serum-free medium and in medium supplemented with delipidized serum. Whereas the growth of four cell lines was inhibited more in serumfree medium, the growth of the Calu-1 cell line was stimulated by ATRA in a dose-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
(55 reference statements)
3
10
0
Order By: Relevance
“…3) (Li et al, 1998) cells, and DPH2L is concomitantly down-regulated during treatment. 3) (Wan et al, 1997;Lee et al, 1997), we observed down-regulation of DPH2L in response to 4HPR but not to all-trans RA. 3) (van der Leede et al, 1993), DPH2L remained constant after these treatments.…”
Section: Reduction Of Dph2l Expression Inhibits Cell Growthmentioning
confidence: 47%
“…3) (Li et al, 1998) cells, and DPH2L is concomitantly down-regulated during treatment. 3) (Wan et al, 1997;Lee et al, 1997), we observed down-regulation of DPH2L in response to 4HPR but not to all-trans RA. 3) (van der Leede et al, 1993), DPH2L remained constant after these treatments.…”
Section: Reduction Of Dph2l Expression Inhibits Cell Growthmentioning
confidence: 47%
“…After RA treatment, the signal intensity was enhanced to 175.33±10.80 (P<0.05, n=6; Figure 2A,2B,2G). Together with CD2366, a RA receptor-selective antagonist [16] , the induction of PCNA by RA expression was overcome. There were no differences of the PCNA expression levels among the control, CD and RA+CD groups.…”
Section: Resultsmentioning
confidence: 99%
“…Retinoids can exert different, and even opposite effects on cell proliferation and differentiation depending on the dose, the cellular context and experimental conditions employed (Wan et al . 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Retinoids can exert different, and even opposite effects on cell proliferation and differentiation depending on the dose, the cellular context and experimental conditions employed (Wan et al 1997). The only differentiative effects of 4HPR were reported in long-term cultures of F9 cells surviving treatment with 1-10 lM 4HPR, which displayed a parietal endoderm morphology resembling RA-treated cells (Clifford et al 1999), and in oesophageal squamous carcinoma cell lines (Muller et al 1997).…”
Section: Discussionmentioning
confidence: 99%